Effect of discontinuing ongoing education and postprescription feedback on antimicrobial prescriptions at discharge from the emergency department - Yasuaki Tagashira (Cambridge University Press, 2022)
Multifaceted intervention is preferrable as an ASP strategy in the emergency department (ED). I assessed the effect of discontinuing multifaceted intervention for antimicrobial prescriptions at discharge in the emergency department. The proportion of appropriate prescriptions decreased quickly after discontinuation. Continuous commitment to appropriate antimicrobial prescriptions is needed for effective antimicrobial stewardship.